Reduction of arsenic level in rice by different preparation and cooking methods - SABUNCULAR, GÜLEREN; İSLAMOĞLU, AYŞE HÜMEYRA; AKTAÇ, ŞULE (My University, 2023)
Rice, a crop that grows underwater, can absorb more arsenic and cause dietary exposure to arsenic. Arsenic levels can be reduced by using different methods. This study aimed to determine the arsenic level in rice by different preparation and cooking methods. Rice was prepared by 4 different preparations and 7 different cooking methods, and arsenic levels were analysed by ICP-MS method. Arsenic level was 0.05 ± 0.009 mg/kg in raw rice, while arsenic levels varied between 0.03 - 0.04 mg/kg in different preparation methods and 0.01 - 0.02 mg/kg in different cooking methods. Arsenic levels decreased with cooking, and the highest arsenic removal percentage was achieved in cooking by filtration and steaming methods (for both 80%). In conclusion, the arsenic level in raw rice was below the reference limits, with the appropriate preparation and cooking methods this amount can be reduced.
Keywords: Arsenic; cooking methods; preparation methods; rice